Technical innovation changes standard radiographic protocols in veterinary medicine: is it necessary to obtain two dorsoproximal–palmarodistal oblique views of the equine foot when using computerised radiography systems?. (21st May 2016) - Whitlock, J.; Dixon, J.; Sherlock, C.; Tucker, R.; Bolt, D. M.; Weller, R.
Abstract : Since the 1950s, veterinary practitioners have included two separate dorsoproximal–palmarodistal oblique (DPr–PaDiO) radiographs as part of a standard series of the equine foot. One image is obtained to visualise the distal phalanx and the other to visualise the navicular bone. However, rapid development of computed radiography and digital radiography and their post‐processing capabilities could mean that this practice is no longer required. The aim of this study was to determine differences in perceived image quality between DPr–PaDiO radiographs that were acquired with a computerised radiography system with exposures, centring and collimation recommended for the navicular bone versus images acquired for the distal phalanx but were subsequently manipulated post‐acquisition to highlight the navicular bone. Thirty images were presented to four clinicians for quality assessment and graded using a 1–3 scale (1=textbook quality, 2=diagnostic quality, 3=non‐diagnostic image). No significant difference in diagnostic quality was found between the original navicular bone images and the manipulated distal phalanx images. This finding suggests that a single DPr–PaDiO image of the distal phalanx is sufficient for an equine foot radiographic series, with appropriate post‐processing and manipulation. This change in protocol will result in reduced radiographic study time and decreased patient/personnel radiation exposure.